Kebutuhan Mahasiswa Fakultas Bahasa dan Seni Terhadap Layanan Referensi di Perpustakaan Universitas Negeri Padang - Retniati, Retniati; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The problems studied in this paper are (1) users opinion about service referenceÂ (2) the user need for service reference. To describe: (1) the user opinion to service reference and (2) the user need about service of reference. This study belongs to qualitative research methodology descriptive data were collected through interviews and observations of service reference. Therefore, sampling data analysis by fortunity. Based on this research, First, users opinion about the service reference, and (1) librarians often leave the room service reference, (2) often the information sought can not be found by pemustaka, (3) unstructured information sources, so it takes a long time to trace. Second, the users need for services of reference, (1) oral (2) written. The conclusions that can be made â€‹â€‹based on the results of the following research first, librarians should not have to leave because his presence is more needed than the existence of a reference collection. Keywords: reference services; need of informations